Cultural Diversity and Conflict in Multicultural Cities - Alaknanda Patel (Fondazione Eni Enrico Mattei (FEEM), 2003)
India has been known as the land of many cultures. Gujarat, an Indian state, has reflected this special aspect for over a millennium. In addition to the people of different religious faith like Hindu, Muslim, Jain, Christian and Zorastrian, various caste groups within the Hindus and migrant workers ensured a diversity of culture and lifestyle. This is especially true in the city of Baroda. This paper studies the dynamics of their coexistence. Gujarat, till about two years ago, was an economically vibrant state with Baroda as its pride. Employment opportunities attracted fresh migration to the city. Despite sporadic troubles among different religious groups there was at least a veneer of calm in Baroda. But early in 2002, violence of an unbelievabld dimension broke out between Hindus and Muslims. This was not a conflict arising out of migration of outsiders but among people of the same soil and similar background, between Hindus and Muslims. With this background the critical factor in spreading the violence was economic. Encroachments on each other's economic turf were unavoidable which in turn became a new source of conflict. There never is a set formula about the relationship between cultural diversity and conflict. Diverse cultures merge into the mainstream partly to avoid conflicts as in the case of tribals whereas in the case of the two major protagonists, Hindus and Muslims, conflict leads to greater attention to difference. In periods of extreme tension in this relationship, economic hardships, spatial pressures, competition for limited resources can lead to conflicts of catastrophic proportions.
Keywords: Z10; 330; India; Migration; Cultural diversity; Coexistence dynamics; Conflict; Economic distress